Short Communication: Molecular bird sexing on kutilang (Pycnonotus sp.) based on amplification of CHD-Z and CHD-W genes by using polymerase chain reaction method - Yudith Violetta Pamulang; Aris Haryanto (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Pamulang YV, Haryanto A. 2021. Short Communication: Molecular bird sexing on kutilang (Pycnonotus sp.) based on amplification of CHD-Z and CHD-W genes by using polymerase chain reaction method. Biodiversitas 22: 449-452. Sex determination is an important aspect in breeding, ecological studies, rearing and reproductive management on Kutilang (Pycnonotus sp.) birds. It is based on differences in intron lengths from DNA amplification of the Chromodomain Helicase DNA-binding (CHD) genes on the Z and W sex chromosomes. This study aims to compare the molecular bird sexing method on Pycnonotus sp. by PCR amplification derived from two different DNA sources. DNA was extracted from DNA 100 µL peripheral blood (1-2 drops) and three plucked feathers from each sample. The CHD genes were amplified using PCR method and visualized by electrophoresis on 1.5% agarose gel. The amplified DNA fragments were single and double DNA bands in the size of 300 bp for the CHD-Z and 400 bp for the CHD-W genes. Three samples were identified as males from the six Pycnonotus sp. while the other three were females. The molecular sexing of six Kultilang (Pycnonotus sp.) birds showed that three samples were males and three were females. Descriptive analysis of two different DNA sources showed that the DNA extracted from peripheral blood samples has better quality than DNA extracted from plucked feathers.